Breeding for Rice Variety Tolerant to Iron Toxicity - Nugraha, Yudhistira; Rumanti, Indrastuti A. (Puslitbang Tanaman Pangan, 2017)
Excess of reduced iron (Fe2+) in the soil affects plant growth of some crops. Iron toxicity is physiological disorder which occurs mostly under flooded condition, where rice is predominantly cultivated. In order to contribute information to the rice breeding program, we review the physiological, genetic and breeding of rice tolerance to iron toxicity. Some rice genotypes were identified as having tolerance to iron toxicity with different mechanism-types. Most of the tolerance variations are local varieties which had adapted to the harst environment of their origin. Those genotypes needed to be improved to be widely adopted by farmers in the targeted areas. Selection for iron toxicity tolerance genotypes faces problems due to the fact that the targeted areas are in remote areas which are difficult to acces. It is important to develop effective and efficient screening technique that able to copy the real field condition. Identification tolerance-type of the genotypes is also very important to develop basic of more prÃ©cises physiological-breeding program. A number of elite lines have been developed in some rice research institution in Indonesia. The genes regulating for iron toxicity tolerance in rice are very complex that it makes difficult to accelerate the selection using molecullar marker. An approach to develop technique of molecullar marker based breeding to iron toxicity tolerance in rice was outlined.